Paparan Lama Internet dan Media Sosial Hubungannya Terhadap Perilaku Seks Remaja - Dhani Syahputra Bukit; R. Kintoko Rochadi; Alam Bakti Keloko (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2024)
Introduction: Problems that dominate adolescence include sexuality, HIV/AIDS, and drugs. sexual behavior of adolescents can hurt their health, both physically, psychologically, and socially, which often ends in unwanted pregnancies, early marriage, abortion, sexually transmitted infections, and other manifestations in the form of increased maternal mortality rates (MMR). Objectives: to examine one of the factors related to adolescents' exposure in shaping their sexual behavior, namely by analyzing the length of internet and social media access of adolescents in a day with adolescent sexual behavior. Methods: This study used a cross-sectional design, using a sample in the study of 170 adolescents in Terjun Village, Medan Marelan Subdistrict which was taken by simple random sampling. the data obtained were analyzed using the chi-square test. Results: show that there is a significant relationship between the length of internet access and adolescent social media in a day with adolescent sexual behavior with a p value = 0.0005 (p ≤ 0.05). Conclusions: To prevent risky sexual behavior in adolescents related to access to the internet and social media, better monitoring is needed from parents and also providing education to adolescents about positive internet access so that all adolescents become wiser in using the internet and social media they have.